45th AIAA Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-2308
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Multiple Vortices over a Double Delta Wing

Abstract: Interactions between strake and wing vortices over a 70/50 double delta wing were studied experimentally in a wind tunnel using particle image velocimetry (PIV) measurements. The upstream effect of the wing vortex on the formation of the strake vortex was identified. A dual-vortex structure of the strake vortices is observed before the wing vortex develops. Prior to vortex breakdown, both wing and strake vortices were found meandering in relatively small regions. The correlation between the instantaneous loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…The POD modes of the baseline case have been extensively discussed in previous studies 9 which revealed the dominant m = 1 helical displacement mode at the trailing-edge for the fully developed afterbody vortex. This same m = 1 mode had previously been identified with wing tip vortices 26,27 , delta wing vortices 28 and inlet vortices 29 .…”
Section: E Proper Orthogonal Decompositionsupporting
confidence: 74%
“…The POD modes of the baseline case have been extensively discussed in previous studies 9 which revealed the dominant m = 1 helical displacement mode at the trailing-edge for the fully developed afterbody vortex. This same m = 1 mode had previously been identified with wing tip vortices 26,27 , delta wing vortices 28 and inlet vortices 29 .…”
Section: E Proper Orthogonal Decompositionsupporting
confidence: 74%
“…Antkowiak and Brancher (2004) proposed the possibility of a relationship between meandering of vortex cores and transient amplification of |m| = 1 disturbances (first helical mode). This mode has been documented in wing-tip vortices (Roy and Leweke 2005;del Pino et al 2011;Chen et al 2016) and leading-edge vortices (Zhang et al 2016;Ma et al 2017). Recently, this mode was measured and also predicted by a spatial stability analysis (Edstrand et al 2016) in tip vortices.…”
Section: Meandering Of Tip Vorticesmentioning
confidence: 72%
“…The two-dimensional POD modes cannot reveal the dominant wavelength. Note that the same first helical mode was also identified in the meandering of the trailing vortices (Roy and Leweke 2005;del Pino et al 2011;Chen et al 2016;Edstrand et al 2016), delta wing vortices (Zhang et al 2016;Ma et al 2017), afterbody vortices (Bulathsinghala et al 2017), and inlet vortices (Wang and Gursul 2012). Higher modes are also shown in Fig.…”
Section: Proper Orthogonal Decomposition (Pod) Analysismentioning
confidence: 75%
“…In the recent times, experiments made by Zhang et al. 13 using PIV on a 70°/50° double-delta wing indicated the upstream effect of wing vortex on the formation of the strake vortex. The formation of the strake and wing vortex, their intermingling and breakdown could be well captured.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have been performed on a round leading-edged double-delta (cropped 80 /45 sweep) wing body model at subsonic and transonic speed by Rao et al, 12 which indicated the complex phenomena emerging due to the strake and wing vortices. In the recent times, experiments made by Zhang et al 13 using PIV on a 70 /50 double-delta wing indicated the upstream effect of wing vortex on the formation of the strake vortex. The formation of the strake and wing vortex, their intermingling and breakdown could be well captured.…”
Section: Introductionmentioning
confidence: 99%